2016
DOI: 10.2522/ptj.20140315
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Independent Walking in Young Children With Cerebral Palsy

Abstract: The ability to transfer from sitting to standing and from standing to sitting predicted independent walking in young children with CP. Prospective longitudinal studies are recommended to determine indicators of readiness for independent walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…All items included in the measure are expected to be accomplished by a typically developing five-yearold child 41 . The items in the test that measure a sit-to-stand activity have been reported to be predictable for independent walking in young children with CP 44 .…”
Section: Disturbances In Movement and Posture In Cerebral Palsymentioning
confidence: 99%
See 2 more Smart Citations
“…All items included in the measure are expected to be accomplished by a typically developing five-yearold child 41 . The items in the test that measure a sit-to-stand activity have been reported to be predictable for independent walking in young children with CP 44 .…”
Section: Disturbances In Movement and Posture In Cerebral Palsymentioning
confidence: 99%
“…In another study Tieman et al (2007) reported that some children preferred to crawl despite their ability to walk 47 . More recently, Begnoche et al (2016) reported that achievement of postural control in sitting or reciprocity in crawling were not good predictors for walking ability in young children with CP 44 . These authors furthermore reported functional strength and dynamic postural control, measured as the ability to attain sitting and standing from a chair, to be a good predictors for walking ability 44 .…”
Section: Motor Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postural control is influenced by factors such as sensory processing (Barela et al., 2011; Pavão et al., 2013), muscle strength, tonus, and anthropometric characteristics (Begnoche et al., 2016; Duarte & Freitas, 2010; Nashner et al., 1983). In children, the degree of influence of these factors might change throughout life, since their anatomical structures and physiological systems are still developing and constantly changing (Steindl et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…10 Use of AFOs to support the development of walking is in line with these aims. However, while the development of walking in children with CP has received some attention in the literature, 11,12 the effect of orthoses on the acquisition of walking in children with CP is unknown. This case study aims to evaluate early intervention with AFOs in a subject with CP, before the onset of independent standing or walking.…”
Section: Introductionmentioning
confidence: 99%